IDENTIFIKASI KEBUTUHAN PENDIDIKAN NON-FORMAL DI KOMUNITAS INDUSTRI: STUDI LAPANGAN DI KAMPUNG PETUNG, KRAGILAN - Pertiwi, Fitri (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
This study aims to identify the non-formal education needs of the industrial community in Kampung Petung, Kragilan. The research employed a descriptive qualitative approach through participatory observation and semi-structured interviews with local residents, community leaders, and informal sector workers. Findings reveal significant challenges in access to formal employment, continuing education, and vocational training. Additional issues include environmental degradation and declining social cohesion. The community requires non-formal education programs such as technical skills training, micro-entrepreneurship, environmental and health literacy, and youth leadership development. The study shows that establishing a community-based non-formal education center is essential to strengthen community resilience and promote inclusive socio-economic transformation.